Pharmacist-led interventions in addressing improper disposal practices of unused and expired household medication: A systematic review - Sofa D. Alfian; Bagus Adhinagoro; Devani O. Winardi; Fidelia Angela; Meliana Griselda; Vesara A. Gathera; Rizky Abdulah (Heliyon, 2024)
Background: Improper household medication disposal practices are a source of significant threat to environmental safety and public health. Pharmacists play a crucial role in mitigating these risks by educating the public about proper medication disposal. Evidence regarding the effectiveness of efforts conducted by health professionals to reduce the risks associated with improper disposal practices is still lacking. Therefore, this study aimed to systematically review pharmacist-led interventions in addressing unused and expired household medication disposal. Method: A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar databases to identify studies evaluating pharmacist-led interventions and the effectiveness in improving household medication disposal practices until January 2024 with no constraints on publication year. Two reviewers independently performed the study selection process, data extraction, and outcomes assessment. Subsequently, the entire collected data were extracted and synthesized using qualitative and quantitative methods. Results: The results showed that two among the total 83 studies retrieved during the search process met the inclusion criteria. The identified pharmacist-led interventions included the provision of an at-home medication disposal kit and an informational handout on proper disposal. However, these interventions showed no significant effects in improving household medication disposal practices, and all studies reported a low engagement rate with interventions. Conclusion: The systematic review identified limited literature on pharmacist-led interventions for unused and expired household medication disposal practices, with no observed significant effects. Active patient and pharmacist engagement were required to enhance the effectiveness of interventions. Furthermore, the included limited studies suggested the need for the development of more pharmacist-led interventions to facilitate the role of pharmacist in educating the public on proper household medication disposal.